Growth perfomance of Tilapia sparmanni fed on formulated chicken feeds - Nsinda Philemon; Tamatamah Rashid (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2019)
Growth performance of 120 fi sh fi ngerlings of Tilapia sparmanni stocked in three rectangular tanks was evaluated after feeding on three different formulated chicken feeds for eight weeks. Fish wet weights and lengths were measured after every two weeks, they indicated considerable increase.